The Uunguu Monitoring and Evaluation Committee: Intercultural Governance of a Land and Sea Management Programme in the Kimberley, Australia. (May 2017) - Austin, Beau J.; Vigilante, Tom; Cowell, Stuart; Dutton, Ian M.; Djanghara, Dorothy; Mangolomara, Scholastica; Puermora, Bernard; Bundamurra, Albert; Clement, Zerika
Summary: The importance of Indigenous peoples' and their ancestral estates for the maintenance and protection of biodiversity, ecosystem function, threatened species and cultural diversity is clear. Due to their nature, processes and tools to measure the impact of intercultural Indigenous land and sea management partnerships need to be innovative and adaptable. In 2015, the Wunambal Gaambera Healthy Country Plan reached its mid‐point, which triggered an evaluation to enable adaptive management through the assessment of effectiveness. The evaluation was used to appraise the need for adaptation, contribute to the evidence base for healthy Country, and to report on achievements. The Uunguu Monitoring and Evaluation Committee, an innovative, intercultural and interdisciplinary body, and their collaborators adopted a multiple evidence‐based approach to enable an enriched picture. This committee has successfully integrated western scientific and local Indigenous knowledge for adaptive management by embodying the principles of co‐production. The Uunguu Monitoring and Evaluation Committee model outlines a way of doing knowledge integration from the bottom up which, given the significance of the cultural and natural diversity of the Indigenous estate, makes a valuable contribution to the global community of practitioners attempting to use diverse knowledges for better management of biodiversity, ecosystems, threatened species and cultural traditions.